2021
DOI: 10.21203/rs.3.rs-576799/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of hospital cleaning services staff towards Coronavirus Disease-2019 (COVID-19) in a Middle Eastern country: A web-based cross-sectional study

Abstract: Background Hospital cleaners are the unsung heroes in the fight against the COVID-19 pandemic. This study aims to assess the knowledge, attitudes, and practices (KAP) of hospital cleaners towards COVID-19 and to determine factors associated with good practices. Methods A cross-sectional study was conducted in Lebanon between 1st and 14th November 2020. Data was collected through an online survey that was sent to governmental-run and private hospitals. The questionnaire consisted of socio-demographic characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Health, safety and environment (HSE) are of critical importance in pharmacies due to their economic, human and ethical impact (19). The study results showed that pharmacists' awareness of pharmacy health principles and issues such as mental, physical and social health is high, which is close to the results of Mihanpour et al (20) and Dalal Youssef is similar to (21) This was about the level of awareness of the hospital staff. The popularity score of the pharmacists was 1456.6 and their average score was 90.725.…”
Section: Discussionsupporting
confidence: 72%
“…Health, safety and environment (HSE) are of critical importance in pharmacies due to their economic, human and ethical impact (19). The study results showed that pharmacists' awareness of pharmacy health principles and issues such as mental, physical and social health is high, which is close to the results of Mihanpour et al (20) and Dalal Youssef is similar to (21) This was about the level of awareness of the hospital staff. The popularity score of the pharmacists was 1456.6 and their average score was 90.725.…”
Section: Discussionsupporting
confidence: 72%